2020
DOI: 10.3390/ijms21228416
|View full text |Cite
|
Sign up to set email alerts
|

Moderate, but Not Excessive, Training Attenuates Autophagy Machinery in Metabolic Tissues

Abstract: The protective effects of chronic moderate exercise-mediated autophagy include the prevention and treatment of several diseases and the extension of lifespan. In addition, physical exercise may impair cellular structures, requiring the action of the autophagy mechanism for clearance and renovation of damaged cellular components. For the first time, we investigated the adaptations on basal autophagy flux in vivo in mice’s liver, heart, and skeletal muscle tissues submitted to four different chronic exercise mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
0
11
0
2
Order By: Relevance
“…Thus, future investigations should compare these physical exercise protocols’ effects considering other skeletal muscle samples and time courses. It is essential to point out that the autophagic flux responses to chronic strength and concurrent exercise protocols have been investigated [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, future investigations should compare these physical exercise protocols’ effects considering other skeletal muscle samples and time courses. It is essential to point out that the autophagic flux responses to chronic strength and concurrent exercise protocols have been investigated [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mice were treated with intraperitoneal injections of colchicine (0.4 mg/kg/day; AB120663, ABCAM, Cambridge, UK) or vehicle (0.9% saline) for 3 consecutive days. The final injection was performed 4 h before the acute physical exercise protocols [ 44 , 68 , 69 , 70 ]. The colchicine treatment inhibits autophagosome degradation, inducing an increase in the levels of LC3II and/or Sqstm1/p62 [ 71 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, Kim et al reported that expressions of LC3II/LC3I was decreased after a single bout of exercise 7 . And Alisson et al reported that chronic exhaustive training reduced the LC3II protein expression 38 . There are several possible explanations for these discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…Portanto, os níveis elevados de insulina para o grupo EE/Rapa podem explicar os níveis mais elevados Diversas investigações utilizando diferentes condições de saúde demonstraram elevação dos marcadores de autofagia no tecido hepático e nas células hepáticas após o tratamento com rapamicina(99)(100)(101)(102)(103), porém é a primeira vez que a combinação entre excesso de exercício e rapamicina é investigada. da Rocha et al(80) demonstraram a redução de vários genes autofágicos no fígado de camundongos submetidos aos protocolos de endurance ou excessivo. Os autores concluíram que o exercício regular de endurance é um fator epigenético que modifica as expressões gênicas autofágicas no fígado a um novo estado basal(80).Para analisar o fluxo autofágico, os roedores receberam colchicina, uma droga bloqueadora do autofagossomo que aumenta o conteúdo de Sqstm1/p62 e LC3 II.…”
unclassified
“…da Rocha et al(80) demonstraram a redução de vários genes autofágicos no fígado de camundongos submetidos aos protocolos de endurance ou excessivo. Os autores concluíram que o exercício regular de endurance é um fator epigenético que modifica as expressões gênicas autofágicas no fígado a um novo estado basal(80).Para analisar o fluxo autofágico, os roedores receberam colchicina, uma droga bloqueadora do autofagossomo que aumenta o conteúdo de Sqstm1/p62 e LC3 II. A ativação autofágica hepática preserva os hepatócitos da morte e lesão celular(104).…”
unclassified